Facile Synthesis of Fluorescent Polymer Nanoparticles by Covalent Modification–Nanoprecipitation of Amine‐Reactive Ester Polymers. Issue 11 (11th March 2015) - Lee, Yeonju; Hanif, Sadaf; Theato, Patrick; Zentel, Rudolf; Lim, Jeewoo; Char, Kookheon; Char, K.; Zentel, R.
<x xml:space="preserve">Abstract</x> Emission wavelength control in fluorescent nanoparticles (NPs) is crucial for their applications. In the case of inorganic quantum dots or dye‐impregnated silica NPs, such a control is readily achieved by changing the size of the particles or choosing appropriate fluorescent dyes, respectively. A similar modular approach for controlling the emission wavelength of fluorescent polymer NPs, however, is difficult. This article reports on fluorescent polymer NPs, the synthesis of which provides a platform for a modular approach towards the preparation of fluorescent NPs of desired emission wavelength. Atom‐transfer radical polymerization (ATRP) is employed to synthesize reactive ester polymers, which are then easily modified with a commercially available dye and subsequently subjected to nanoprecipitation. The resulting NPs, with low size polydispersity, show an enhanced emission quantum yield when compared with the same dye molecules in solution.